2009
DOI: 10.1155/2009/498505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of a Silver‐Hydroxyapatite Nanocomposite

Abstract: A silver-hydroxyapatite nanocomposite has been obtained by a colloidal chemical route and subsequent reduction process in H2/Ar atmosphere at350∘C. This material has been characterized by TEM, XRD, and UV-Visible spectroscopy, showing the silver nanoparticles (∼65 nm) supported onto the HA particles (∼130 nm) surface without a high degree of agglomeration. The bactericidal effect against common Gram-positive and Gram-negative bacteria has been also investigated. The results indicated a high antimicrobial activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 41 publications
1
63
0
3
Order By: Relevance
“…Silver aggregates on HAp particles have been reported during synthesis of Ag-HAp nanocomposites, using a colloidal chemical route and subsequent reduction in H 2 /Ar atmosphere at 350°C. This has been attributed to partial destabilization of HAp in aqueous suspension favoring the growth of Ag 2 O nuclei (Diaz et al 2009). Chung et al (2006) also reported the presence of Ag 2 O crystallite phase in addition to the HAp and the nitrate phases, depending upon the degree of substitution by silver.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Silver aggregates on HAp particles have been reported during synthesis of Ag-HAp nanocomposites, using a colloidal chemical route and subsequent reduction in H 2 /Ar atmosphere at 350°C. This has been attributed to partial destabilization of HAp in aqueous suspension favoring the growth of Ag 2 O nuclei (Diaz et al 2009). Chung et al (2006) also reported the presence of Ag 2 O crystallite phase in addition to the HAp and the nitrate phases, depending upon the degree of substitution by silver.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity for Ag nanoparticles is reported in the range 1.69-100 lg/ml for various bacterial cultures (MarambioJones and Hoek 2010; Kvitek et al 2008;Kim et al 2011;Sondi and Sondi 2004). Silver based HAp nanocomposites have been shown to exhibit antimicrobial activity in growth medium where the Ag concentration ranges from 10 to 70 lg/ml for Gram-negative and Gram-positive cultures (Diaz et al 2009;Rameshbabu and Prasad Rao 2007). In this study, Ag-HAp exhibited antimicrobial activity at a much lower silver concentration of 7 lg/ml against E. coli and at 15 lg/ml for S. aureus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations